Detection of Ludic Patterns in Two Triadic Motor Games and Differences in Decision Complexity - Aguilar, Miguel Pic; Navarro-Adelantado, Vicente; Jonsson, Gudberg K. (Frontiers in Psychology, 2018)
The triad is a particular structure in which an ambivalent social relationship takes place. A chasing games model was followed, with rules, and in two different structures (A↔B↔C↔A and A→B→C→A) on four class groups (two for each structure), for a total of 84, 12 and 13 year old secondary school students, 37 girls (44%) and 47 boys (66%). The aim was to examine if the players’ behavior, in relation to the triad structure, matches with any ludic behavior patterns. An observational methodology was applied, with a nomothetic, punctual and multidimensional design (Anguera, Blanco, Hernández-Mendo and Losada, 2011; Anguera, 2003). The intra and inter-evaluative correlation coefficients and the generalizability theory ensured the quality of the data. A mixed behavioral role system was used (4 criteria and 17 categories), and the pattern detection tool Theme (Magnusson, 2000) was applied. The results show that time location of motor responses in triad games was not random. In the ‘maze’ game we detected more complex ludic patterns than the ‘three fields’ game, which might be explained by means of structural determinants such as circulation. This research points out the decisional complexity in motor games, and it confirms the differences among triads from the point of view of motor communication.